Flexible fate determination ensures robust differentiation in the hair follicle. Issue 12 (December 2018) - Xin, Tianchi; Gonzalez, David; Rompolas, Panteleimon; Greco, Valentina
Abstract Tissue homeostasis is sustained by stem cell self-renewal and differentiation. How stem cells coordinately differentiate into multiple cell types is largely unclear. Recent studies underline the heterogeneity among stem cells or common progenitors, suggesting that coordination occurs at the stem cell/progenitor level1–4 . Here, by tracking and manipulating the same stem cells and their progeny at the single-cell level in live mice, we uncover an unanticipated flexibility of homeostatic stem cell differentiation in hair follicles. Although stem cells have been shown to be flexible upon injury, we demonstrate that hair germ stem cells at the single-cell level can flexibly establish all of the differentiation lineages even in uninjured conditions. Furthermore, stem cell-derived hair progenitors in the structure called matrix, previously thought to be unipotent, flexibly change differentiation outcomes as a consequence of unexpected dynamic relocation. Finally, the flexible cell fate determination mechanism maintains normal differentiation and tissue architecture against an ectopic differentiation stimulus induced by Wnt activation. This work provides a model of continual fate channelling and late commitment of stem cells to achieve coordinated differentiation and robust tissue architecture. Xin et al. track stem cells in live mice to show that fate determination is a flexible process during homeostatic hair follicle growth, and progenitor cells can change differentiation outcomes as a consequence of dynamic relocation.